On assessing an organization’s preparedness to adopt and make use of Big Data - Mach-Król, Maria (Business Informatics, 2016)
In the paper it is proposed to enrich the Big Data Temporal Maturity Model with a self-assessment form, based on Likert’s scale. The issues of an organization’s maturity in the Big Data context are presented, the Big Data Temporal Maturity Model (BDTMM) is briefly outlined, and the self-assessment form is presented and discussed. The main aim of this paper is to introduce a Big Data Temporal Maturity Model, and to present an assessment form accompanying the model. Both the model and the form have been elaborated by the author of the paper. The assessment form is based on the well-known Likert scale, and thus enables the interested organizations to check at which point of the route leading to the full use of Big Data they are now, and what they can do to progress
Informatyka Ekonomiczna = Business Informatics, 2016, Nr 1 (39), s. 75-82
Keywords: maturity model; Big Data; self-assessment; Likert’s scale; model dojrzałości; samoocena; skala Likerta